Implementasi Program Jawa Timur Pemberdayaan Usaha Perempuan (JATIM PUSPA) di Desa Sumberkolak Kecamatan Panarukan Kabupaten Situbondo - Usrotul Hasanah; Sendy Dharma Alfiana (Majalah Ilmiah DIAN ILMU, 2022)
Jatim Puspa is a trading business program that is given to people affected by Covid-19 and this Jatim Puspa program is specifically given to women, so that women can take part in economic recovery amid the Covid-19 pandemic in Sumberkolak Village, Panarukan District, Situbondo Regency. The research method used is descriptive research method with a qualitative approach. By making observations about a natural phenomenon by collecting data using the method of observation, interviews, and documentation. The research location was conducted in Sumberkolak Village, Panarukan District, Situbondo Regency. It can be concluded that Sumberkolak Village, Panarukan District, Situbondo Regency has implemented the Jatim Puspa Program well, but it has not been maximized, especially in terms of conveying information, selecting program recipients and monitoring.